Rice bran cooking oil production a plant design - Camacho, Gina Lyn Q.; Cruz, Aiza D.; Reyes, Mark Jayson P.
Rice bran oil is vastly superior to traditional cooking oils and can be considered a nutraceutical oil that is good for healthy cooking needs. It is obtained from rice bran and was found to contain significant amount of antioxidants that contributes to the reduction of the amount of cholesterol present in human body. Rice bran oil has the ideal balance of saturated, monounsaturated and polysaturated fats as recommended by organization such as American Heart Association and World Health Organization. It has a very high smoke point, making it perfect for deep frying and is a premium choice for the replacement of hydrogenated oil containing trans-fatty acid. The objective of this plant design is to shed some light on the potential of a full-scale local rice bran cooking oil production, which, until the time of writing, has never been established in our country. The said plant will utilize some of the latest findings and methodologies in vegetables oil extraction and refinery. The production process proposed in this study consist of various oil extraction and refining techniques applied by some leading rice bran oil producers in Asia. The process is divided into three phases. Phase I is concerned with the preparation of the rice bran. It involves the process of screening, steam cooking and dying. On the other hand, Phase II is concerned with the separation of crude rice bran oil from rice bran. It involves mainly the oil extraction process. And finally, Phase III is concerned in transforming the crude rice bran oil into refined rice bran oil or edible rice bran oil. It involves the process of dewaxing, degumming, neutralization, bleaching, winterization, filtration and deodorization. In this stage, the unsaponifiables, colour and pigments, waxes, gums, free fatty acids and other unwanted substance present in the crude rice bran oil were removed. The proposed process in this study has the advantage of increasing the recovery of crude rice wax and deoiled rice bran and deactivation of the lipase enzymes which deteriorates the oil. The proposed process design has a production rate of 45 metric tons/day of rice bran oil (RBO). This production rate needs an annual production cost of around 3.7 Billion pesos and yields a net profit of around 8 Billion pesos. From these results, it can be concluded that rice bran oil is good venture for a rice producing country such as the Philippines.